Monitoring the compliance of sailing ships with fuel sulfur content regulations using unmanned aerial vehicle (UAV) measurements of ship emissions in open water - F. Zhou (Atmospheric Measurement Techniques, 2020)
Due to technical and cost limitations, the monitoring of emissions from ships sailing in open water within ship emission control areas (ECAs) is relatively rare. The present study adopts a monitoring method involving an unmanned aerial vehicle (UAV) that takes off from a patrol boat to measure the concentrations of SO2 and CO2 within the plumes of sailing ships. Our method aims to provide a low-cost, remote approach for estimating the fuel sulfur content (FSC) of sailing ships in open water, which overcomes the limitations of ground-based and small-aircraft-based methods. The selected monitoring area was the Yangtze River estuary, a domestic ECA with an FSC limit of 0.5 % (m∕m) implemented by the Chinese government. A total of 27 sailing ships were monitored, 12 of which were found to have an FSC of >0.5 % (m∕m). Moreover, the FSCs of the sailing ships were found to be higher than those of berthing ships in the study area. Based upon the online monitoring results, four of the monitored ships were intercepted by maritime law enforcement, and fuel samples were collected and analyzed in a laboratory; the results confirmed that all four FSCs were >0.5 % (m∕m). Among them, one offending ship was tracked down on 15 July 2019; this was the first time that a sailing ship had been caught for having failed the FSC regulations in China. Overall, the present study provides scientific support for evaluating the effectiveness of ECA policies and recommends that emissions from sailing ships be monitored more often in open water in the future.